EFFECTIVENESS OF THE APPLICATION OF ECOLA METHOD IN CRITICAL READING COURSES FOR STUDENTS OF PBSI 2019A IKIP BUDI UTOMO MALANG - Endang Setyowati; Lis Susilawati (Journey: Journal of English Language and Pedagogy, 2023)
The use of the ECOLA method in this study was to detect the effectiveness of critical reading skills in PBSI 2019A IKIP Budi Utomo Malang students. This type of research is PTK research with the Kemmis and Mc models. Taggart. This study used PBSI class 2019A student subjects as many as 30 students. Data collection techniques using qualitative and quantitative techniques. Qualitative data were obtained by conducting interviews and observations, while for quantitative data obtained from student pretests which were then calculated using the average formula. From the results obtained after implementing the Ecola method in learning critical reading it is very effective. Improvements can be seen from the ongoing learning process and also the results of the reading skill itself. Students also enjoy and are more active in participating in class learning, as well as the material provided by lecturers, students can understand it well. The results of improving critical reading skills using the ECOLA method can be seen from the significant increase in student scores. The average pre-test score was 76.5 for the first cycle, which was 78.6, and for the second cycle, it was 80.2. In addition, the number of students who achieved success indicators in the pre-action was 10 students, at the end of the first cycle there were 19 students, and at the end of the second cycle there were 27 students out of 30 students.